BIMBINGAN PRIBADI-SOSIAL UNTUK SELF-EFFICACY SISWA DAN IMPLIKASINYA PADA BIMBINGAN DAN KONSELING DI SMK DIPONEGORO SLEMAN YOGYAKARTA - Atifah Hanum (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
The reason for this investigation is to portray the execution of individual social direction for understudies at SMK Diponegoro, Depok, Sleman, Yogyakarta and to depict individual social direction for growing high self-viability and fortifying low self-adequacy for understudies at SMK Diponegoro, Depok, Sleman, Yogyakarta. The sort of exploration utilized is subjective quantitative examination. The strategy utilized in this examination is meeting, scale, and documentation. The consequence of this exploration is that the execution of individual social direction administrations comprises of 4 phases, specifically the arranging stage, execution stage, assessment organize and follow-up. The type of the execution of individual social direction administrations at Diponegoro Professional School with backhanded strategies incorporates old style direction, joint effort with homeroom instructors, home visits, IKMS, and direction sheets. The material introduced incorporates inspiration, self-assurance, confidence, self-change, and controlling feelings. The type of execution with the immediate technique incorporates singular direction, bunch direction, and individual guiding. Individual social direction for the turn of events and reinforcing of understudies' self-adequacy got a decent reaction with a normal score of 86.7.